Does Power Always Flow to the Executive? Interbranch Oscillations in Legislative Authority, 1976–2014. Issue 1 (31st January 2023) - Chaisty, Paul; Power, Timothy
Abstract: Is legislative power flowing to the executive branch over time? Beginning in the 1990s, comparativists began to investigate delegation to the executive under different executive formats. Hypothesized causes include collective action problems due to legislative fractionalization, the presence of a dominant pro-executive faction, preference congruence vis-à-vis the head of government, and challenges posed by economic crises. We test these four hypotheses on a data set containing 2, 020 country-year observations of democracies and semi-democracies between 1976 and 2014. Using V-Dem data, we derive annualized measures of shifts in executive–legislative relationships. Contrary to stereotypes of executive dominance, relative gains by legislatures are no less frequent than gains by executives, and economic crises do not advantage political executives in consistent ways. Surprisingly, some of the factors expected to benefit executives seem to enhance assembly authority as well. Robust democracy maintains interbranch power relations in equilibrium, while lower levels of polyarchy are associated with greater 'noise' in the relationship.